Population dynamics, intensity of damage and management of the coreid bug, paradasynus rostratus dist. - Ambily Paul (Department of Agricultural Entomology, College of Agriculture, 2006)
Experiments were conducted to study the influence of alternate hosts on the population dynamics of the coreid bug, Paradasynus rostratus Dist. and consequent damage to coconut and to evolve an eco-friendly management strategy to the pest. An abstract of the work done and the results are given below. A survey conducted in Thiruvananthapuram district to study the incidence and intensity of coreid bug infestation on coconut revealed that the infestation was the highest in the coastal region. The incidence was lower in the upland and midland regions. Among the variety of crops seen in the coconut based homesteads, guava, cashew, cocoa and neem were recorded as potential hosts of the pest. Studies on the influence of alternate hosts on the population build up of coreid bug revealed that the alternate hosts were a major determinant in the extent of infestation of coreid bug on coconut. The pest multiplied on the alternate hosts during flushing, flowering and fruit formation stages of the crops and subsequently shifted to the base crop, coconut in multiple cropping systems. The changes in size and yield parameters of nut due to the infestation of P.rostratus were assessed. Nuts with negligible damage (category II) did not show any significant difference in nut shape, nut characters, copra and oil content. Significant reduction in copra and oil was observed in moderately (category IV) and , heavily (category V) damaged nuts. The endosperm was not at all formed in severely damaged (category VI) nuts. The changes in the biochemical constituents of coconut buttons due to feeding of coreid bug were studied. The phenol content in young infested nuts recorded an increase compared to healthy nuts. A progressive reduction in starch and fibre content of young nuts was obtained with increase in degree of infestation The study on the effect of infestation of P.rostratus on germination and vigour of seedlings revealed that though all the nuts in damage category II (negligible